On a method of tuning of couplers for electron LINACS based on disk loaded waveguides - Aizatskyi, N.I.; Kramarenko, K.Yu.; Khodak, I.V.; Kushnir, V.A.; Mytrochenko, V.V.; Opanasenko, A.M.; Perezhogin, S.A.; Selivanov, L.I.; Zhiglo, V.F. (Вопросы атомной науки и техники, 2015)
The article presents an adjustment procedure for an input and output couplers of a traveling wave accelerating section based on cylindrical disk loaded waveguide (CDLW). The procedure consists in bead pull measurement of on axis field and calculation of reflection from the coupler under adjustment using the field values at three points separated by a geometric period of the adjacent CDLW. Description of a model for coupler tuning as well as tuning results also are presented.